Money counts : revisiting economic calculation - Schmidt, Mario (Postdoctoral fellow); Ross, Sandy (College teacher) (Studies in social analysis ;, 2020)
"Traditionally viewed as an abstraction, the quantative nature of money is essential in evaluating the relationship between monetary systems and society. On the Qualities of Quantity moves beyond abstraction, exploring the conceptual diversity and everyday enactment of money's quantity. Drawing from case studies including British jewelers, blood money payments in Germanic law codes, and the quotidian use of money in cosmopolital Moscow, a Western Kenyan village, and socialist Havana, the chapters in this volume offer new theoretical and empirical interpretations of money's quantative nature as it relates to abstraction, sociality, materiality, freedom, and morality"--